The geometry of social networks - Mackisack, Daniel (AUC Knowledge Fountain, 2019)
This thesis is primarily about the impact of the Egyptian revolution on the social realities of those who experienced it. How it changed their lives and how it reshaped society. It looks at the relationship between the geometry of the social in Cairo and the experience of political events and regime changes in Egypt between 2010 and 2016, drawing from the individual assemblages and narratives of participants and their associations with diverse people and places. It covers a period beginning prior to the revolution on January 25th 2011 and concludes in the more recent post-revolutionary period. Individual participants were surveyed on the distribution and diversity of their close social relationships in each of 5 distinct periods during this time, aligning with 5 phases of political change. Authoritarianism persists on the basis of cultural hegemony, networks and practices which inhibit social actualization and the formation of social capital and solidarity between diverse social groups. In this fashion, heterogeneous individuals, communities and experiences of social, cultural and economic realities may remain unshared and isolated from one another. It therefore becomes more difficult to achieve the kind of complex and sustained solidarity or social capital necessary for democratic practice to develop and function. Both democracy and authoritarianism are seen as more than simply regime types, but states which are sustained or undermined by the geometric structure of relations. From the combination of data gathered and discussed in this thesis, distinct patterns emerge in the social lives of those who experience political change. Some of which have the effect of undermining authoritarianism, while others reinforce it. By creating a picture of social geometry, using an interview methodology rooted in Actor Network Theory, this thesis creates a platform for analyzing the impact of political change in terms of both social capital and social solidarity. It also allows us to discuss the broader implications of these changes and to reassess the way in which we conceive of democracy in an increasingly complex world.